The Influence of Education, Returns, and Motivation On Students' Interest In Investing in The Islamic Capital Market Indonesia - Rijadi, Puti Khairani; Budi, Yeniasari Rizkia (Adpebi International Journal of Multidisciplinary Sciences, 2022)
Purpose – This study is to determine the influence of education, returns, and motivation on student interest in investing in the Islamic capital market. Methodology/approach – This study used purposive sampling with several predetermined criteria, the results obtained 63 students who were used as samples. Data analysis was tested by multiple linear regression using SPSS 25. Findings – It was found that the investment motivation variable (X3) affects investment interest, while the education and return variables have no effect. However, from the results of simultaneous tests, all independent variables used affect the dependent variables. Novelty/value – The values from this study is that the growth of the Islamic capital market, which has increased every year, can arouse investors' interest in setting aside some of the assets owned in the Islamic capital market. The attractiveness of the Islamic capital market is not only among business people but has begun to be seen by the millennial generation. Keywords: Education, Return, and Motivation